Computer graphics techniques : theory and practice - Rogers, David F.; Earnshaw, Rae A., 1944-; British Computer Society. Computer Graphics and Displays Group; Computer Graphics Society; International Summer Institute on the State of the Art in Computer Graphics (1988 : University of Exeter) (New York : Springer-Verlag, 1990)
57